STRATEGI PENINGKATAN KAPASITAS APARATUR DALAM MENGOPTIMALKAN PELAYANAN PUBLIK - A.M. Yadisar (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Capacity building of local government apparatus is a strategic step in facing increasingly complex public service challenges. A competent and professional apparatus is needed to support responsive, transparent, and quality services. This research aims to explore strategies to increase the capacity of the apparatus through training approaches, bureaucratic reform, utilisation of information and communication technology, and multi-stakeholder collaboration. The research method used is qualitative with a descriptive approach, involving in-depth interviews, documentation studies, and observation. The results show that competency-based training programmes, adaptive bureaucratic reforms, digital infrastructure development, and participatory approaches are key factors in improving apparatus capacity. However, challenges such as budget constraints, resistance to change, and competency gaps between agencies are still obstacles that need to be overcome. This study recommends the importance of consistent policy support, strengthening cross-sectoral cooperation, and periodic evaluation to ensure the sustainability of the apparatus capacity building programme. With the right strategy, it is expected that optimal public services and good governance can be achieved.